Hubungan Antara Aktivitas Fisik dengan Kedisiplinan Anak Kelompok B di TK Pertiwi 1 Getas Kabupaten Nganjuk - Indri Wulan Suryani; Titin Faridatun Nisa'; Yulias Wulani Fajar (Universitas Trunojoyo Madura, 2017)
Learning in early childhood has been done through studying and playing activities. Based on the result of pre-observations in TK Pertiwi 1 Getas found that the teachers do the learning process through fun physical activities to develop children's physical motoric. Physical activities are expected to develop the children’s indirectly i.e. submissive and orderly in the game of physical activities. The physical activities are like jump rope game, trains game, ducts ball, throwing ball, gymnastics, and zig-zag running. The physical activities are based on Standards Rate of Achievement Child Development aged 5-6 years. This study is purposed to determine the correlation between physical activities and children’s discipline. This study uses quantitative approach and correlational research techniques. The technique of collecting data is through observations, interviews, and documentations. The data analysis is using Pearson Product Moment Correlation. The research subject of this study is the 27 students of group B. The results of data analysis found the correlation value is 0.29 and the contribution of physical activities and children’s discipline is 8.41%. The data analysis shows a low correlation between physical activities and children’s discipline. The low correlation is caused by the teachers have been growing the discipline through habituation in learning process.